Fake news e eleições: impacto da desinformação e das novas tecnologias no pleito eleitoral do Brasil - Silva, Rennan Gonçalves (2024)
The sociopolitical changes that took place over the last 21st century, especially in Brazil, brought with them a special problem regarding the form and access to information. Fruit of the medium, the term "fake news" has become a word in the global order, characterizing this phenomenon in the post-truth universe, when verifying the accentuated proliferation of false news that circulate in the communication and relationship networks. In fact, although many believe the term "fake news" is new, it is not, dating back to the late 19th century. The general objective of this research is to analyze the existence of a democratic crisis and to identify, through a comparative study, the legal tools available to combat disinformation. In addition, it seeks to promote a discussion on the importance of facing and holding accountable the spread of false news in electoral processes, aiming to protect the full exercise of citizenship and individual autonomy. In the elaboration process of this study, the methodology of a deductive approach will be adopted, centered on an extensive bibliographic survey that substantiates the major themes addressed here. For this, the main fundamentals and theories inherent to the study of Law and its intersections with new technologies were taken as a basis. A brief examination of different legal and regulatory approaches applied in different national and international contexts will be carried out, with the aim of identifying good practices and proposing effective solutions to deal with disinformation. At the end of this research, it is expected to contribute to the academic and legal debate on disinformation and its impact on contemporary democracies. In addition, it is intended to provide insights for the formulation of public policies and the improvement of existing legislation, with the aim of guaranteeing the protection of democratic values and the safeguarding of citizens' rights in the context of elections.